School Readiness in Children: Types and Correlation with Duration of School Preparation Activities - Lubovsky D.V (Moscow State University of Psychology and Education, 2019)
The article presents results of a study on personal readiness for school in children aged 6-6,5 years who engaged in school preparation activities for different periods of time either at kindergarten only or at any additional classes as well. It was assumed that longer periods of school preparation would be associated with lower levels of school motivation in children entering school. The study involved 80 preschoolers aged 6 to 6,5.The following techniques were used: the conversation "Internal position of the student" (by N.I. Gootkina), the technique for academic motivation research in first-graders (by M.R. Ginzburg), Raven's Coloured Progressive Matrices, the first subtest of the Kern-Jirasek School Maturity Test (drawing of male figure), and the author's questionnaire about the forms and duration of school preparation activities (for parents).The outcomes of the study showed that those children who began preparing to school early and continued attending school preparation activities for much longer than a year had lower levels of school motivation and, therefore, lower levels of personal readiness for school. Interestingly, there were no significant differences in intellectual readiness between them and the children with shorter school preparation experiences. The paper concludes with discussing the practical applications of the present study.